PD-1 blockade as a future treatment for colorectal cancer with microsatellite instability - Diana Maria Leite da Cunha Russo (2020)
Introduction: Colorectal cancer is the third most common cancer worldwide, with about 15% of these tumours related with microsatellite instability, which confers distinct characteristics to these tumours, both clinicopathological and in the response to treatments. In fact, the poor response to chemotherapy in these tumours has led to the investigation of new treatments, with immunotherapy being the most successful one to date. The focus of this review is to assess the response of microsatellite unstable colorectal cancer to PD-1 blockade, and the mechanisms behind that response. Methods: A PubMed research was conducted, resulting in the inclusion of 47 articles in this review. Results: Microsatellite instability results in a high neoantigen load, leading to a highly active immune microenvironment of the tumour, mainly due to T cells. To counteract this, there is an upregulation of PD-1, acting as a "brake" for immune cells, facilitating tumour growth and metastasis. This upregulation makes these tumours great candidates for treatment with PD-1 blockade, as seen in many clinical trials, where the overall responses and progression free survival rates were higher than those observed in microsatellite stable tumours. Conclusion: With the importance of colorectal cancer with microsatellite instability new treatments are necessary. Therefore, PD-1 blockade is a promising treatment for colorectal cancer with microsatellite instability, with improvement in survival rates and a better prognosis for these patients.